Laparoscopic vs open surgery in gastric GISTs larger than 5 cm: A systematic review and meta-analysis - Francisco António Pita de Araújo (2022)
Background and Aims: Surgical resection represents the main treatment for resectable non-metastatic gastric GISTs. Despite the feasibility and safety of laparoscopic resection, its standard use in tumors larger than 5 centimeters is yet to be established . The aim of this study is to compare the current evidence on laparoscopic resection with the classical open surgical approach in terms of perioperative, postoperative and oncological outcomes in tumors larger than 5 centimeters. Methods: The PubMed, Scopus, and Web of Science databases were consulted. Articles eligible for this review and meta-analysis included randomized controlled trials (RCTs) and observational non-randomized clinical trials, published until January 2022, that compared the approach to gastric GISTs larger than 5 centimeters by open and laparoscopic surgery. A post-hoc subgroup analysis based on the extent of the surgery was performed for the outcomes operative time, blood loss and length of hospital stay. Results: A total of nine studies met the eligibility criteria. 246 patients undergoing laparoscopic surgery (LAP) and 301 patients undergoing open surgery (OS) were included. The laparoscopic approach had statistically significant lower intraoperative blood loss (p=0.01) and times to oral intake (p<0.01), to first flatus (p<0.01) and of hospital stay (0.01), than the OS approach. No significant differences were found when operative time (0.25), postoperative complications (0.08), R0 resection (0.76), and recurrence rate (0.09) were evaluated. The comparative subgroup analysis between studies that included any type of surgical technique and those that only included atypical gastrectomies (wedge resection), could not explain the substantial heterogeneity obtained in the respective outcomes. Conclusions: Compared to the open surgical approach, the laparoscopic approach in GISTs larger than 5 centimeters is a technically safe and feasible surgical method with similar oncological results. These results are motivating for the development of further studies, ideally prospective and randomized.